Paulo Freire and transformative education - Paula Allman; Elizabeth Lange Christensen; Peter Mayo; Sue M. Scott; Daniel Schugurensky (Adult Education Research Conference, 1996)
The purpose of this symposium is to pay tribute to Paulo Freire, one of the most influential theorists and practitioners in adult education and pedagogy in general. The first presentation provides a general background to Freire’s work and it is followed by an exposition of Freire’s central concept of ‘Conscientization’. The discussion will then highlight two key strands in Freiere’s work, namely the Marxian and Liberation Theology strands. The concluding section addresses Freire and postcolonial politics. Paulo Freire : from Pedagogy of the Oppressed to Pedagogy of Hope (Daniel Schugurensky) Conscientization as the Object of Practice (Sue M. Scott) Freire with no Dilutions (Paula Allman) Freire and Liberation Theology (Elizabeth Lange Christensen) Paul Freire and the Colonial Legacy (Peter Mayo)